Մհեր–Միհրի առասպելի շերտը հայկական ժողովրդական հեքիաթներում - Մարտոյան, Գագիկ («Զանգակ - 97»)
From materials of one of a cycle of the Armenian magic fairy tales becomes clear, that the hero. closed in a mountain. Arev Manuk (Child Sun ) is the samc as Low Mher - Mithra, and his father is the same as David of Sasun of the Armenianepos "The Mads of Sasun". The latter, as well as his son Low Mher andh is father High Mher too was considered as the god by the Sun. For the ancicnt Armenians Mithraism was expressed in a worship of three suns - morning s, day time's and evening\s. Arev Manuk is the evening sun, which every day is closing down behind a mountain and occurring at the night - in an image of the moon.
Keywords: Բանասիրություն